2020
DOI: 10.2174/1573399815666190321144310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dipeptidyl Peptidase-4 Inhibitors in Kidney Transplant Recipients with Post-transplant Diabetes Mellitus (PTDM)- a Systematic Review and Meta-Analysis

Abstract: Background: Kidney transplant recipients may develop post-transplant diabetes mellitus (PTDM). Dipeptidyl peptidase 4(DPP-4) inhibitors are evolving agents in the management of patients with diabetes mellitus. Aims: To evaluate the efficacy and safety of DPP-4 inhibitors in the management of post-transplant diabetes mellitus (PTDM) in renal transplant recipients. Methods: We performed a systematic search of the electronic databases using keys words and Mesh terms. Data were extracted and reviewed using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Among these novel anti-diabetic medications, sodiumglucose cotransporter-2 (SGLT-2) inhibitor and dipeptidyl peptidase-4 (DPP-4) inhibitor are the ones that are currently widely used [5][6][7][8][9]. Compared to prior anti-diabetic medications (e.g., sulfonylurea), these medications not only effectively reduce blood glucose level, but are also associated with lower risk of hypoglycemia and have reported better clinical outcomes [10,11]. The mechanisms underlying these benefits are likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Among these novel anti-diabetic medications, sodiumglucose cotransporter-2 (SGLT-2) inhibitor and dipeptidyl peptidase-4 (DPP-4) inhibitor are the ones that are currently widely used [5][6][7][8][9]. Compared to prior anti-diabetic medications (e.g., sulfonylurea), these medications not only effectively reduce blood glucose level, but are also associated with lower risk of hypoglycemia and have reported better clinical outcomes [10,11]. The mechanisms underlying these benefits are likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 meta-analysis of five studies investing gliptin use in patients with PTDM after renal transplant suggested that they are safe and effective at reducing HbA1c without affecting eGFR or tacrolimus level. 102 …”
Section: Oral Hypoglycaemic Agents In Dialysis and Kidney Transplant Patientsmentioning
confidence: 99%
“…101 A 2019 meta-analysis of five studies investing gliptin use in patients with PTDM after renal transplant suggested that they are safe and effective at reducing HbA1c without affecting eGFR or tacrolimus level. 102 GLP-1 analogues GLP-1 analogues mimic the incretin GLP-1 to stimulate glucose-dependent insulin secretion.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…In fact, VIDPP-4i may modulate T-cell differentiation and promote immune tolerance by selectively inhibiting effector T cells and upregulating Tregs, potentially allowing for reduction of immunosuppressant dose and immunosuppression-related toxicity. In this context, the use of DPP-4i may also be advantageous in terms of reduced glucotoxicity and preservation of beta-cell function among patients with T1D who underwent kidney, pancreas or islet transplantation, and patients with post-transplant diabetes [233].…”
Section: Synergistic Anti-inflammatory and Immunomodulatory Effects Of Vitamin D And Dpp-4 Inhibitors: Mechanistic Evidencementioning
confidence: 99%